Impact of IFRS on Bank’s Loan Loss Provision Decision: An Empirical Study of Hong Kong SAR and Japan - Zhao, Kehan (2013)
This thesis investigates the loan loss provisioning behaviors of banks in Hong Kong and Japan, especially associating with the income smoothing, capital management, signaling effect and the pro-cyclicality. Beyond the level of providing the evidence for the existence of those provisioning behaviors above, this study also examines the potential influence on them caused by distinct accounting standards which generally involve the GAAP and IFRS. Overall, 36 banks have been selected over the period of 2005-2012 to reflect the general situation of the usage of loan loss provisions in Asia. Notably, 16 banks in Hong Kong and 20 banks in Japan have been chosen to conduct a comparable test between an IFRS adopter (HK) and a GAAP adopter (Japan). A quantitative analysis through GMM estimation is employed. The findings illustrate that only the presence of the capital management could be verified and the absence of income-smoothing behaviors and signaling mechanism is also proved. In terms of the smoothing income, a countercyclical tendency to the business cycle has been found. However, the pro-cyclicality nature of loan loss provisions among the sample banks from a macroeconomic perspective remains to be inconclusive. When it refers to the impact induced by the adoption of IFRS on the loan loss provisioning behaviors, an amplified effect has been represented in aspect of income smoothing, signaling and pro-cyclicality. Only the capital management behavior is restrained under the adoption of IFRS. The potential illustration could provide an inspiration for the banks or countries which tend to make prudential decision on whether adopting IFRS or not.